Comparative study of peri-operative outcome following laparotomy versus laparoscopic technique of abdominal hysterectomy for benign gynaecological lesions - Gavhane, Satyajit P.; Bhavsar, Dhruval K.; Bangal, Vidyadhar B.; Gagare, Swati D.; Kodlikeri, Amey R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Laparoscopic technique of hysterectomy is becoming increasingly popular in developing and developed world. Laparoscopic hysterectomy is a minimal access procedure that allows patients to recover faster. The study was undertaken to assess the impact of two abdominal techniques (laparoscopic and conventional laparotomy) on various variables like operative time, hospital stay, complications and convalescence period. Methods: An observational longitudinal study was carried out at tertiary care centre. Two hundred and ten women, as per inclusion and exclusion criteria, who had undergone abdominal hysterectomy for benign uterine pathology, either by laparotomy (Group A) or by laparoscopic technique (Group B) during study period were included. Data was analyzed and compared by using different variables between two methods of hysterectomy, using percentages and Chi square test for normal distribution. P value less than 0.05 was considered significant. Results: The mean duration of surgery was 100 minutes in group A and 175 minutes in Group B. There were two cases (1.90%) of minor injury to urinary bladder in Group A and one case (0.95%) of thermal injury to urinary bladder in Group B. The mean blood loss was around 240 ml and 70 ml in Group A and B respectively. The need for postoperative analgesia was observed in 100% cases from Group A and 38.09% from group B. The average duration required for out of bed ambulation was 25 hours and 14 hours in Group A and B respectively. The mean hospital stay in group A and B was 7.5 days and 3.5 days respectively. Conclusions: Following laparoscopic hysterectomy, women had less morbidity, less need for post-operative pain relief, had early ambulation, short hospital stay and early resumption of routine activities at home as compared to women who had undergone abdominal hysterectomy by conventional method.